CD32B1, a versatile non-signaling antibody-binding scaffold for enhanced T cell adhesion to tumor stromal cognate antigens - Feigelson, Sara W.; Dadosh, Tali; Levi, Nehora; Sapoznikov, Anita; Weinstein-Marom, Hadas; Blokon-Kogan, Dayana; Avraham, Yahel; Unger, Tamar; Gross, Gideon; Dahan, Rony; Alon, Ronen (Frontiers in Immunology, 2025)
Targeting cytotoxic T lymphocytes (CTLs), as chimeric antigen T cells (CAR-T), T cell receptor-engineered (TCR)-T cells or adoptive cell transfer of tumor infiltrating T cells (TILs) to solid tumors is a major therapeutic challenge. We describe a new strategy to confer these lymphocytes with de novo adhesiveness to surface proteins enriched in the tumor microenvironment. This approach is based on decorating CTLs with monoclonal antibodies (mAbs) specific to any surface protein of interest within the stroma and the extracelullar matrix of solid tumors. For efficient mAb decoration, we have introduced a mAb binding Fc receptor (FcR) scaffold, FcγRIIB1 (CD32B1), which we found to be enriched on B lymphocyte microvilli (MV). This isoform contains an inhibitory ITIM motif within a cytoplasmic tail anchored to the cortical cytoskeleton. We thus generated a non-signaling CD32B1 mutant lacking the ITIM motif (termed ITIM-less CD32B1, or ILCD32B1) and successfully expressed it in human T cells which normally do not express this FcR. The ILCD32B1 expressing lymphocytes bound multiple IgG1 mAbs whose Fc domain was engineered with a 5-residue substitution to reach a nM range of Fc-FcγCR dissociation constants. The mAb decorated ILCD32B1 expressing T cells could readily adhere to a surface-bound cognate antigen. To broaden the utility of this scaffold, we have also generated a new fusion protein in which the entire Fc binding domain was truncated (tILCD32B1) and replaced with a monomeric streptavidin variant, mSA2, via a CD8 hinge. The molecule, termed mSA2-CD8h-tILCD32B1, was also successfully expressed in T cells, readily and stably bound biotinylated IgG mAbs in vitro and once decorated with the biotin labeled mAbs, conferred the T cells with high adhesiveness to multiple surface-coated antigens. mSA2-CD8h-tILCD32B1 expressing human T cells decorated ex vivo with a biotin-labeled mAb retained the antibody for hours after accumulation inside breast tumors implanted in immunodeficient recipient mice. Our results collectively suggest that a non-signaling CD32B1 can be used as a versatile scaffold for mAb decoration of T cells. Our mAb decoration approach can confer new cell adhesive reactivities to improve tumor CTL (CAR-T and TIL) accumulation and retention inside solid tumors.